Sendeng-4 Suppressed Melanoma Growth by Induction of Autophagy and Apoptosis. (24th August 2021) - Du, Rina; Zhao, Pengwei; Wu, Shikui; Gao, Yaoxing; Wu, Rina; Yang, Minli; Song, Wanying; Gao, Haining
Abstract : Sendeng-4 is a traditional Chinese medicine that has been successfully applied to anti-inflammatory diseases in clinical practice. Monomers within Sendeng-4 showed promising antitumor activity against lung cancer, colon cancer, and cutaneous cancer. However, potency of Sendeng-4 in melanoma has not been explored. This study aims to explore the potential application of Sendeng-4 in melanoma treatment. In the present study, we systemically investigate the possibility of Sendeng-4 for treatment of melanoma cancer in vitro by proliferation assay, colony formation, flow cell cytometry, RNA-seq, western blot, and fluorescence-based assay. Our data demonstrated that Sendeng-4 suppresses the proliferation and colony formation capacity of melanoma cells and induces cell cycle block at G2/M phase and eventually cell death. Mechanistically, transcriptome sequencing demonstrates that the PI3K-AKT pathway was significantly inactivated upon Sendeng-4 exposure, which was confirmed by western blot showing decreased phosphorylation of AKT. In addition, decreased BCL-2 expression and increased BAX expression were observed, suggesting programmed cell death via apoptosis. Moreover, LC3-II production as well as autophagosomes formation was observed as demonstrated by western blot and immunofluorescence, indicating elevated autophagy network by Sendeng-4 stimulation. Collectively, we concluded that Sendeng-4 might be used as an anticancer drug for melanoma.